Update on the diagnosis and management of malignant phyllodes tumors of the breast. (June 2017) - Strode, Matthew; Khoury, Thaer; Mangieri, Christopher; Takabe, Kazuaki
Abstract: Malignant phyllodes tumors of the breast are a rare entity. They occur infrequently but most often in younger women in comparison to typical epithelial-based breast cancers. Treatment of these tumors is not without controversy and in this review we will present an update on the diagnosis and management of malignant phyllodes tumors of the breast. Highlights: Surgical margin review and discussion. Role of radiation and systemic therapy. Pathogenesis and differentiation between similar fibroepithelial tumors.